The hanging of the crane / by Henry Wadsworth Longfellow ; with illustrations. - Longfellow, Henry Wadsworth, 1807-1882. (Tufts University. Tisch Library., 2016)
1 online resource (1 preliminary leaf, [vii]-x, [6], 17-64 pages) : illustrations.; First American edition.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: BAL12166